Polyacrylic acid polymers hydrogels intended to topical drug delivery: preparation and characterization. (June 2015) - Calixto, Giovana; Yoshii, Ana Carolina; Rocha e Silva, Hilris; Stringhetti Ferreira Cury, Beatriz; Chorilli, Marlus
Abstract Context: Bioadhesiviness of polyacrylic acid polymers make them promising hydrogels to design topical drug delivery systems, allowing a close contact with biological substrate as well as an enhanced local concentration gradient, both factors that may improve the biological performance of the drugs. Aim: Texture and bioadhesive properties of hydrogels were assessed by using texture analyzer and they were correlated with their rheological behavior and performance as drug delivery systems. Methods: Aqueous dispersions of both polymers were prepared at 0.5%, 1.0% and 1.5% w/v. Hardness, compressibility, adhesiveness, cohesiveness, bioadhesion, continuous flow, oscillatory dynamic test and in vitro drug release were evaluated. Results: Rheological and texture parameters were dependent on polymer concentration and C974P polymer built the strongest structures. Both 1.5% hydrogels presented high bioadhesion values. About 50% of the metronidazole (MTZ) was sustained released from hydrogels within 2 h with an initial burst release at early stage. After, the release rates were decreased and 10% of the MTZ was released in the next 10 h. The drug release process was driven by Fickian diffusion and complex mechanism for PP and C974P hydrogels, respectively. Conclusion: The set of results demonstrated that these hydrogels are promising to be used as topical controlled drug delivery system.